2019
DOI: 10.3390/cancers11081153
|View full text |Cite
|
Sign up to set email alerts
|

Main Inflammatory Cells and Potentials of Anti-Inflammatory Agents in Prostate Cancer

Abstract: Prostate cancer is the most common type of cancer and the leading cause of cancer deaths among men in many countries. Preventing progression is a major concern for prostate cancer patients on active surveillance, patients with recurrence after radical therapies, and patients who acquired resistance to systemic therapies. Inflammation, which is induced by various factors such as infection, microbiome, obesity, and a high-fat diet, is the major etiology in the development of prostate cancer. Inflammatory cells p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 158 publications
1
33
0
Order By: Relevance
“…Therefore, regional differences in obesity rates might contribute to differences in the incidence of high-risk PCa. Moreover, obesity resulting from a high-calorie diet causes chronic systemic inflammation and might be involved in PCa growth through immune system-related mechanisms [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, regional differences in obesity rates might contribute to differences in the incidence of high-risk PCa. Moreover, obesity resulting from a high-calorie diet causes chronic systemic inflammation and might be involved in PCa growth through immune system-related mechanisms [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tumor-inltrating macrophages have been shown to favor progression in various tumors. 5,6 A previous study demonstrated that inhibition of M2-like macrophages prevents osteosarcoma cell initiation and stemness. 7 Intriguingly, several studies conrmed that macrophages showed positive outcomes of osteosarcoma patients during diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic systemic inflammation, which is associated with the risk of several cancer types, including breast, colon, and pancreatic cancer, has been attributed to lifestyle [ 117 ]. Hayashi et al found that medications and diets that modulate the immune status or suppress the inflammatory response, such as metformin, aspirin, nonsteroidal anti-inflammatory drugs, statins, and soy isoflavones, may be clinically beneficial for patients with prostate cancer [ 118 ].…”
Section: Types Of Cancermentioning
confidence: 99%